Diversity and Distribution of the Mangrove Gastropods of Kuala Selangor Nature Park, Selangor - Jahid, A; R Singh, H (International Journal of Engineering and Technology, 2019)
This study reports on the diversity and distribution of mangrove gastropods from Kuala Selangor Nature Park sampled from August to November 2017. The line transect with quadrat method was employed to sample gastropods which were handpicked from the various mangrove structures (root, stem, branch) and mangrove floor within 5m x 5m quadrats. Nineteen gastropod taxa were recorded from the Bruguiera, mixed (Bruguiera, Avicennia & Rhizophora), and Avicennia & Rhizophora zones. The Ellobiidae (Elobium aurisjudae and Cassidula aurisfelis), Potamidae (Cerithedia obtusa, Cerithidea cingulata and Telescopium telescopium), Muricidae (Chicoreus capucinus) and Naticidae (Nerita balteata) were the most distributed gastropod families at the study site. Gastropod horizontal distribution varied between tree zones (Bruguiera; Bruguiera-Avicennia-Rhizophora; and Avicennia-Rhizophora) and tree type (Brugueira, Rhizophora and Avicennia), while gastropod vertical distribution varied based on height on tree (0 â€“ 120cm) and sub-habitats (roots, floor and trunk) as shown by the principle components analysis (PCA) biplots. The Margalefâ€™s species richness (D=2.90) and Shannon-Weiner diversity (Hâ€™=2.32) was low which is typical of mangroves that are mature while Pielouâ€™s evenness (J=0.77) was high implying lack of dominance by specific gastropod taxa. Â Â